PATIENT AND BYSTANDER PERCEPTION ON THEIR SAFETY DURING HOSPITALIZATION ??T THE LIKAS HOSPITAL - Pn. Tay SM; Pn. Sania L; Pn. Winia S; Pn. M I rida A.; Pn. Nancy; Mat. Rose Chu; Kl Maureen Y.; JT Roseminah P; JT V Cheristy T.; JT Flora G; Mat. Norty B, (The Malaysian Journal of Nursing (MJN), 2009)